PENGEMBANGAN TEKS CERITA BERGAMBAR PADA KETERAMPILAN MEMBABACA SISWA TEMA 7 KEBERSAMAAN SUBTEMA 1 KEBERSAMAAN DI RUMAH PEMBELAJARAN KE 1 - Rizma Siti Nurul Aryani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Picture story text is a text that contains a story accompanied by pictures or illustrations to support the contents of the story. Reading is a useful activity that can provide various information. In Indonesia reading skills are still relatively low. This study aims to obtain a picture story text product Theme 7 Togetherness Sub-theme 1 Togetherness in the 1st Learning House in class II SDN Cibeureum 02 with a total of 20 students. This development uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research results from the validation tests of linguists, material experts, and media experts show that illustrated story texts are valid and very feasible to use by obtaining an average percentage of 89%. In the limited trial phase, as many as 20 students gave a positive response to the illustrated story text used. Based on the results of the research, it can be concluded that the illustrated story text developed in this study proved to be valid, interesting, and very appropriate for use during the learning process.